Odpowiedzi

2010-01-14T23:11:11+01:00
(-1/-½+(-½)³)*8/25=
(-1*(-2)-1/8)*8/25=
(2-1/8)*8/25=
1i7/8*8/25=
15/8*8/25=
3/5


pierwiastek z -4*(-1)³+12*1/6-5*(-6)=
pierwiastek z -4*(-1)+2+30=
pierwiastek z 4+2+30=
pierwiastek z 36=
6
2010-01-14T23:13:06+01:00
1. (-1/x +x³) * 8/25 = dla x = -1/2

(-1/x +x³) * 8/25 =
( - 1 * (-2) + (-1/2)³) * 8/25 =
8/25 * (2 - 1/8) =
16/25 - 1/25 =
15/25 = 3/5 = 0,6


2.pierwiastek z -4x³ + 12y - 5z= dla x = -1 , y=1/6 , z= -6

pierwiastek z -4x³ + 12y - 5z =
pierwiastek z -4 * (-1)³ + 12 * 1/6 - 5 * (-6) =
pierwiastek z -4 * (-1) + 2 + 30 =
pierwiastek z 4 + 2 + 30 =
pierwiastek z 36 =
6

pozdrawiam :)